Economics of the Organic Food Industry in Florida - Thu-Vi Nguyen; Allen Wysocki; Danielle Treadwell (EDIS)
FE732, an 8-page illustrated fact sheet by Thu-Vi Nguyen, Allen Wysocki, and Danielle Treadwell, delivers an overview of the organic industry in Florida, covering the definition of organic, requirements for organic certification, issues in the Florida organic industry, and major market outlets for organic products. Includes references. Published by the UF Department of Food and Resource Economics, September 2008.